(untitled) (Research, Society and Development, 2021)
Introduction: This article aims to analyze the place of Physical Education from GEO Juan Antonio Samaranch Municipal School’s reality. The study summarizes the current school scenario, namely the value of the School Institution in the context of Rio de Janeiro, as an overview for a broader reflection. Method: The investigation is characterized by a qualitative research of sociocultural nature. The study occurred in the period between February and November of 2018. The research used the Information Triangulation technique and Multimethod Approach. The analytical matrix of the investigation composes theoretical lenses of the sociologists Norbert Elias and Pierre Bourdieu, along with the inductive interpretation that emerges from the Critical Discourse Analysis. Results and discussion: In this framework, it is observed that the symbolic Sport capital, of Physical Education, previously understood as a positive social differentiation, lost space in Brazilian public agenda with the end of sports mega-events. In this wake of thoughts, there are strong indications that suggest that the school unit, in vogue, is just the appendix of this axis of tensions; the microsocial reflex of the “Denied” of sports mega-events. Final considerations: In this disposition, it is identified that the investigated unit is a school that seeks to shield its practices while rejecting the anti-culture and the driving forces that currently destabilize the integral education of students, especially those whose school is the only pedagogically oriented learning space. However, GEO Juan Antonio Samaranch is still an exception; it does not portray the chaotic scenario of most municipal schools in Rio de Janeiro.